Classification and Description of "YOU" in Indonesian Related with "YOU (KAMU)” in Plural - Tatu Siti Rohbiah (Loquen, 2017)
Abstract: Many forms of greeting in Indonesian language (twenty-three kinds) in the second pronoun (six kinds) and kinship terms (seventeen kinds) reflects many strata in Indonesian society that is "feudalistic" in which different languages such as the use of greeting used to speak or greet the other person who has different strata or classes. This paper is a comparative analysis of both forms of pronouns and kinship terms are used as a form of greeting in Indonesian as a substitute for "you" in English. Provide classification and description of both pronouns and kinship terms are used as a form of greeting to do with the dimension of "you" in terms of quantity, formality, and gender.